Analisis Peran Otonomi Daerah terhadap Kesejahteraan Masyarakat - Mauliza Nur Fadhillah; Marliyah Marliyah (JIKEM: Jurnal Ilmu Komputer, Ekonomi dan Manajemen, 2022)
The purpose of granting the widest possible autonomy to regions in regional administration is to realize the expectations of community welfare through service improvement, community empowerment, and participation. In addition, it is hoped that the regions can increase their competitiveness through broad autonomy by taking into account the potential and regional diversity of the Unitary State of the Republic of Indonesia as well as democracy, equity, and justice as well as privileges and specializations.Community development and welfare are the main issues in the context of equitable development in order to accelerate the process of improving people's welfare throughout Indonesia. This can be seen from the efforts made by the central and regional governments to plan development in order to obtain optimal results while taking into account local conditions.